Hubungan career pathing dan kualitas hidup sosial ekonomi dengan komitmen dan profesionalisme perawat - Yusnaini Kumalasari; Sukarmin Sukarmin; Heny Siswanti (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Nurses are professionals who play a central role in providing high-quality healthcare to patients. Low levels of commitment and professionalism among nurses can have a direct impact on the hospital’s reputation and the quality of care received by patients. Purpose: To analyze the influence of career pathing and socio-economic quality of life on the commitment and professionalism of nurses. Method: This is a correlational analytical study. The study population comprised all nurses at Aisyiyah Kudus Hospital, totalling 133 nurses. The sample size was 100 nurses, selected using inclusion and exclusion criteria, namely nurses who were permanent staff and had been working for over one year. This study utilised questionnaires on career pathing, socio-economic status, nurses’ commitment, and nurses’ professionalism. Data analysis employed the Spearman’s rank correlation test Results: The study findings indicate that the majority of respondents reported a ‘good’ career pathing category, totalling 66 (66%). Regarding quality of life, 72% were in a ‘good’ socio-economic condition. The majority of respondents demonstrated high commitment (49, 49%) towards their work and exhibited a high level of professionalism (47, 47%). Conclusion: The results of the study indicated that career pathing (p=0.000; r=0.623) and socio-economic quality of life (p=0.000; r=0.551) influence nurses’ commitment at Aisyiyah Kudus Hospital, while career pathing (p=0.000; r=0.549) and socio-economic quality of life (p=0.000, r=0.638) influence on nurses’ professionalism at Aisyiyah Kudus Hospital   Keywords: Career Pathing; Commitment; Profesionalism; Quality Of Life.